2022
DOI: 10.3390/s22155691
|View full text |Cite
|
Sign up to set email alerts
|

Smart Active Vibration Control System of a Rotary Structure Using Piezoelectric Materials

Abstract: A smart active vibration control (AVC) system containing piezoelectric (PZT) actuators, jointly with a linear quadratic regulator (LQR) controller, is proposed in this article to control transverse deflections of a wind turbine (WT) blade. In order to apply controlling rules to the WT blade, a state-of-the-art semi-analytical solution is developed to obtain WT blade lateral displacement under external loadings. The proposed method maps the WT blade to a Euler–Bernoulli beam under the same conditions to find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In order to overcome the shortcomings of the iterative method, many techniques [23] for choosing the parameters of the LQR controller are used. In the recent decades , a GA has been chosen for successful application in vibration control [2,13,[19][20][21][22].…”
Section: Control System Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to overcome the shortcomings of the iterative method, many techniques [23] for choosing the parameters of the LQR controller are used. In the recent decades , a GA has been chosen for successful application in vibration control [2,13,[19][20][21][22].…”
Section: Control System Designmentioning
confidence: 99%
“…One of the ways applied to control actively the vibrations is to use smart materials such as piezoelectric materials as actuators [1]. Hashemi et al [2] propose a smart AVC system for wind turbine blades, utilizing piezoelectric actuators and Linear Quadratic Regulator LQR. The proposed smart control system efficiently suppresses the vibration peaks along the wind turbine blade, and the maximum flap-wise displacement belonging to the tip of the structure is successfully controlled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the intelligent bionic algorithm has broad application prospects in solving complex problems of nonlinear system in active vibration suppression. Hashemi [39] et al proposed a smart active vibration control (AVC) system containing piezoelectric actuators.…”
Section: Pzt Sensor Bladementioning
confidence: 99%
“…The development of smart materials has been reported for many vibration control applications, such as interactive actuators, shape memory alloys (SMA) [ 12 , 13 ] controlled by operator-based design [ 14 ], piezoelectric materials in the form of PZT actuators [ 15 ], piezoelectric sensors [ 16 , 17 ], and so on. Shape memory alloys (SMA) as interactive actuators have proven to be particularly beneficial in comparison to other actuation technologies when incorporated in applications demanding strict adherence to a set of compatibility (e.g., mechanical, biological, weight) and environmental limitations.…”
Section: Introductionmentioning
confidence: 99%